DIFFERENTIATED INSTRUCTION IN ENGLISH LANGUAGE PEDAGOGY AT VOCATIONAL HIGH SCHOOLS IN SOUTH SUMATRA: A MIXED-METHODS STUDY - Dodi Irawan; Hadiyanto; Bunga Ayu Wulandari; Eddy Haryanto (Indonesian EFL Journal, 2026)
This research explores the application of differentiated instruction in English Language Teaching (ELT) at Vocational High Schools (VHS) in South Sumatra, using a sequential explanatory mixed-methods approach. A survey was conducted with 267 English teachers to assess their perceptions, instructional practices, and readiness to implement differentiated teaching within the context of the Emancipated Curriculum. The survey instrument exhibited excellent reliability (Cronbach’s Alpha = 0.983). Quantitative data were analyzed through descriptive and inferential statistics, including correlation and regression, to examine the relationships between differentiated practices, student engagement, and learning outcomes. To complement the quantitative findings, qualitative data were collected through semi-structured interviews, classroom observations, and document analysis from ten selected teachers in both public and private vocational schools. The thematic analysis revealed that teachers employed strategies such as flexible grouping, adaptive materials, scaffolded tasks, and diverse assessments. Despite these efforts, challenges like limited preparation time, varying student levels, insufficient institutional support, and inconsistent understanding of differentiation remained. The study indicates that while differentiated instruction enhances student engagement and supports personalized learning, its implementation is inconsistent. It emphasizes the need for ongoing professional development, stronger institutional support, and better alignment with the Emancipated Curriculum to optimize ELT practices in vocational education.